IDENTIFICATION OF POTENTIAL SOIL DEGRADING MICROBIALS CONTAMINATED WITH INSECTICIDES - Zhusna Nisha Maulida; Nafrida Noor Azkiya; Lailatuz Zahro; Alfini Siska Dewi Handayani; Tara Puri Ducha Rachmani; Arnia Sari Mukaromah (Universitas Medan Area, 2022)
The high use of insecticides can cause soil contamination in the rice field environment, so a solution is needed to reduce the contamination and the negative impact on human health. One of the efforts that can be done to overcome this problem was by bioremediation. The bioremediation technique was chosen due to it is eco- friendly, efficient, and cost-effective in its application. However, bioremediation relies on the capacity of living organisms to absorb, accumulate, translocate and detoxify pollutants in a polluted environment. The objective of this study is to explore microbes that can be used as bioremediation agents in soil exposed to various types of insecticide contamination. The results of this study was as many as Â±56 species of microbes can be used as bioremediation agents for various types of insecticides so that bioremediation needs to be carried out in order to avoid pesticide residues on soil and agricultural products.